Replacing LNT: The Integrated LNT-Hormesis Model. Issue 2 (13th April 2020) - Kaminski, Cara Y.; Dattoli, Michael; Kaminski, Joseph M.
Many scientists and regulators utilize the linear no-threshold (LNT) relationship to estimate the likelihood of carcinogenesis. The LNT model is incorrect and was adopted based upon false pretenses. The use of the model has been corrupted by many to claim that even the smallest ionizing radiation dose may initiate carcinogenesis. This claim has resulted in societal harm.